Utilization of inorganic probes for evaluation of -tocopherol content by EPR Spectroscopy in olive oil - Drouza, Chryssoula; Dieronitou, Anthi; Nicolaou, Xenia; Hadjiadamou, Ioanna (My University, 2025)
VV and/or VIV coordinated catalytic sites are able to activate phenolics in the lipophilic matrix of oil mediated by dioxygen activation; in this oxidative environment free radicals are trapped by -tocopherol to give -tocopheryl radicals monitored by X-band cw-EPR vs time provide very useful quantification tool for the determination the ability of the complexes to initiate radicals1. The possibility to quantify α-Tocopherol in extra virgin olive oils by EPR spectroscopy has been investigated using vanadium (V) lipophilic metal complexes as radical initiators and for the dioxygen activation, targeting fat peroxidation1. In this investigation, the experimental results showed that there is a linear relationship between the intensity of the signal of the α-Tocopheryl radical in the EPR spectrum and the concentration of α-Tocopherol contained, upon addition, in commercial samples of olive oil. This method has been applied on five extra virgin olive oils. In most samples, the α-Tocopherol concentration values determined for the olive oils were very close to the actual values determined by the 19F NMR method2.
Keywords: Vanadium; alpha-tocopherol